Una interpretación simbólica del Arco de don Pedro Manuel en la Catedral de León - García Álvarez, César (Estudios humanísticos. Geografía, historia y arte, 1998)
The so called Bishop Pedro Manuel's arch, in the Cathedral of León, has a rich iconographical decoration, made up mainly by grotesques. The symbolic interpretation of these ornaments, based on the meanings that the neoplatonic philosophy and the Renaissance culture assigned them, reveals the existence of a coherent dimension of meaning that allows to read the whole arch as a iconic exaltation of the humanistic personality of the "mecenas"(patron), specially of his belief on the eternal life, granted at the same time by his Christian faith, and by a probable trust on the neoplatonic ideas.